The Impact of Fogging Activities on Dengue Hemorrhagic Fever (DHF) Prevention in Balocci District - Rahmilah, Mitha; Mujtahidah (Journal of Scientific Insights, 2025)
. Dengue Hemorrhagic Fever (DHF) continues to pose a serious public health challenge in Indonesia, particularly in tropical regions with high population density and poor sanitation. The disease, transmitted primarily by Aedes aegypti mosquitoes, has shown a significant increase in recent years. One of the government’s primary interventions to reduce transmission is fogging, which targets adult mosquitoes as a rapid control measure. However, its long-term effectiveness remains debated if not combined with source reduction strategies. A quantitative descriptive study with a cross-sectional design was conducted in January 2025, involving 477 community respondents selected through total sampling. Data were collected using a questionnaire on the implementation of fogging and perceptions of its effectiveness via the Kobocollect application. The Chi-Square test confirmed a significant association between fogging implementation and community perceptions of its effectiveness in dengue prevention (0.000; p < 0.05). These findings indicate that fogging plays a positive role in controlling dengue transmission. However, its long-term effectiveness requires community participation in mosquito breeding site eradication (PSN 3M Plus) and the integration of environmental management, health education, and sanitation improvements to achieve sustainable dengue prevention.